Obesity is not strongly associated with increased risk for febrile neutropenia during levofloxacin prophylaxis in patients with hematological malignancies receiving intermediate-risk myelosuppressive chemotherapy. (September 2020) - Kurtti, Amanda; Fritz, Kelly; Elofson-Disney, Kathryn; Benefield, Russell
Levofloxacin given at a standard dose of 500 mg daily is recommended for antibacterial prophylaxis in patients receiving myelosuppressive chemotherapy. Obese patients have been shown to exhibit enhanced clearance of levofloxacin and may be at risk for prophylactic failure. This single center, retrospective cohort study from June 2014 to May 2017 evaluated adult patients with estimated creatinine clearance ≥50 mL/min receiving their first cycle of a National Comprehensive Cancer Network defined intermediate-risk regimen. Primary endpoint was incidence of febrile neutropenia. Secondary endpoints included 30-day mortality and the correlation between estimated levofloxacin area under the concentration–time curve and rates of febrile neutropenia. Febrile neutropenia occurred in 26 patients: 12 (35.3%) obese and 14 (21.9%) non-obese ( P  =   0.16). Six (23.1%) of these patients required intensive care, but there were no deaths within 30 days of a febrile neutropenia event. Estimated creatinine clearance was similar between obese and non-obese patients (median 97.5 vs. 91.8 mL/min, P  =   0.39), as was estimated levofloxacin area under the concentration–time curve (median 85.6 vs. 90.8 mg×h/L, P  =   0.39). There were no significant associations between body weight-related variables – total body weight (median 83.4 vs. 80.6 kg, P  =   0.51), body mass index (mean 29.6 vs. 26.8 kg/m 2, P  =   0.35), or body surface area (1.98 vs. 1.99 m 2, P  =   0.68) – and febrile neutropenia in this cohort of patients with similar renal function. Obesity should not be a justification for more aggressive levofloxacin dosing schemes when used for febrile neutropenia prophylaxis.